Treatment outcome of patients with first treatment failure of newly diagnosed pulmonary tuberculosis and with the systemic inflammatory response syndrome - R. M. Yasinskyi (Zaporozhye State Medical University, 2017)
More severe course of disease on patients with first treatment failure of newly diagnosed pulmonary tuberculosis causes the prerequisites for the occurrence of the systemic inflammatory response syndrome (SIRS) in such patients. Aim. To evaluate the treatment outcome of patients with newly diagnosed pulmonary tuberculosis treatment failure, depending on the presence of SIRS at the beginning of treatment. Materials and methods. We examined 49 patients, which were divided into 2 groups. The first group (SIRS-TFNT) included 17 patients who had SIRS at the beginning of treatment. Group 2 (TFNT) consisted of 32 patients, who did not have SIRS. SIRS in patients at the beginning of treatment was diagnosed if 2 or more criteria by R. Bone et al. (1992). Results. Tuberculosis was revealed while examination of patients with complaints in 94.1 % in the 1st group and in 62.5 % - in the 2nd, p ˂ 0.05, the average time of the previous fluorography in the 1st group was 7.4 ± 1.5 years, and in the 2nd - 3.8 ± 0.7 years, р ˂ 0.05. Disseminated, fibrous-cavernous tuberculosis, caseous pneumonia dominated among patients from SIRS-TFNT group (together their proportion was 70.6 %), and infiltrative tuberculosis - among patients from TFNT group (68.8 %), p ˂ 0.05. In patients from the 1st group multiple cavities were determined more often: 35.3 % versus 6.3 %, p ˂ 0.05. More often their size was ˃ 3 cm, p ˂ 0.01. After the intensive phase of treatment destruction did not heal in 77,4 % of patients in the 2nd group, but they decreased to ≤ 2 cm, while in the 1st group the proportion of such patients was only 35.3 %, p ˂ 0.05. Among patients who had adverse reactions in 60 % from the SIRS-TFNT group and only in 11.8 % from the TFNT group they were severe, p ˂ 0.05. The total duration of the intensive phase was 183.5 ± 8.5 days for patients from the 1st group and 165.0 ± 6.5 days from the 2nd group, p ˂ 0.1. Conclusions. This indicates the importance of evaluation the presence of SIRS at the beginning of treatment, since it affects not only the course of the disease in patients with risk of ineffective treatment, but also determines the effectiveness of the treatment.